Using synchrotron radiation to study iron phases in Saharan dust samples from Athens skies - Chatzikonstantinou, N.; Mertzimekis, T. J.; Godelitsas, A.; Gamaletsos, P.; Nastos, P.; Goettlicher, J.; Steininger, R. (HNPS Advances in Nuclear Physics, 2019)
The Sahara desert is the largest source of dust in the world. Saharan dust is characterized by great com- plexity, composed mainly of mixtures of mineral phases (amorphous or crystalline, with particle sizes of the order of μm or even nm). The presence of amorphous components makes it difficult to detect their struc- ture. For this purpose the spectroscopic technique of X–ray absorption fine structure μ–XAFS combined to ultrabright synchrotron SR microbeams is suitable. SR’s main advantage is the recording of spectra in a very short time. In this paper we focus on the study of forms of iron deposited on southeast Mediterranean Sea and mainland of Greece by the waves of Saharan dust. Data collection was carried out at the premises of ANKA (KIT, Germany) on the beamline SUL–X of the environmental research laboratory with advanced X–ray spectroscopic techniques, μ–XRF, μ–XRD and μ–XAFS. Results from the measurements and the simulated spectrum are presented.